PENGGUNAAN TEKNIK PICTURE-CUED UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS - Dwigustini, Retno; Nisa, Baiatun; Susilawati, Susilawati; Hodijah, Uung (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
The research aimed at improving students’ speaking skill using picture-cued technique. Classroom action research with 3 cycles was employed. The research subject consisted of 20 students of tenth grade. The technique of data collection consisted of observation, test and interview. The finding signified that the students’ speaking skill is improved. In cycle I, only 70% of students passed the passing grade. In cycle 2, 90% passed the grade and in cycle 3, 100% passed the grade. The significant of this research did not only explore about picture-cued technique but also identified students’ response of the application of picture-cued technique in English speaking learning. The result of the research showed students’ positive responses to the use of the technique. This further means that the implementation of picture-cued is successful in enhancing students’ speaking skill.